USAHA ORANG TUA DALAM MEMBANTU MENINGKATKAN PRESTASI BELAJAR ANAK DI SDN 021 TARAI DESA TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Vitraningsih, Dhiny; Maemunaty, Titi; Wilson, Wilson (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine parents' efforts to improve children's learning performance at 021 Tarai SDN, Tarai Bangun Village, Tambang District, Kampar Regency. The sample in this study was 55 people, namely class V parents at SDN 021 Tarai. The technique to collect data using a questionnaire. Data analysis techniques using percentage calculation. The results of this study indicate that the efforts of parents to provide adequate learning facilities according to the ability and needs of the school are very high. Moreover, the efforts of parents in creating a learning culture at home are quite high. In addition, parents' efforts to set priorities for tasks directly related to learning in schools are quite high. Moreover, parents' efforts to understand what the school has, will and will be done to develop children's potential are relatively low.Key Words: Parents' Efforts, Improve Learning Performance